Guyton and Hall textbook of medical physiology - Hall, John E. (Saunders/Elsevier, 2011)
Presents complex physiologic principles. With colour artwork, this textbook reflects modern medicine and science, and a range of online extras. It helps in mastering essential human physiology knowledge